Design of Cockles Cleaning and Grading Machine Using Cost Based Method - Zakaria, Muhammad Alim; Muhd Nor, Nik Hisyamudin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Cockle is one of the seafood that Malaysian people love to eat and from this news, it shows that cockle industry is important in Malaysia because of the high demand. The lack of technologies in this industry has made the production of the industry limited and cannot meet the demand that will be needed. This study is to design a machine to clean and grading cockles-based cost to enhance the production of the industry. The design is simple where there are two stages to clean the cockles by using the drum rotating method and supported by burst water pipe to ensure the cleaning efficient and the next stage is by using the grading machine with using sieve method to separate the cockles by different size. The design and simulation of the machine has been carried out using a SolidWorks application. The machine that has been designed will help the small business company to growth by using the affordable machine in producing the cockles that have been cleaned and graded.